PERANAN KEGIATAN PEMANENAN KAYU DALAM MENINGKATKAN PENDAPATAN MASYARAKAT SEKITAR HUTAN: KASUS DI KPH SUKABUMI DAN KPH CIANJUR - Ishak Sumantri; Sukadaryati Sukadaryati (Jurnal Penelitian Hasil Hutan, 2003)
Timber harvesting activities in Perhutani areas are conducted  with the involvement of people living around the forest.  An  investigation was conducted  to find  out the role of timber harvesting activities  in increasing the income of people involved. The results showed that 1) People living around the forest were involved in felling, skidding, and collecting  log in temporary logyard; 2) Workers involvement were temporary and their wage system were differed from location to location. In Sukabumi,  the whole work contract system was applied with the income ranging from Rp 109.800 to  187.417/person/compartment or  Rp  13.725  to Rp 23.500/person/day.  In Cianjur,  the piece  work system was applied with income ranging from Rp 97.788 to 179.166/person/compartment   or Rp 5.750 to Rp 10.500/person/day; and 3) The income obtained from  timber harvesting activities still can not significantly  increase worker's income and, therefore, it is necessary to furthur seek a proper model suitable for the need of temporary and low income workers to participate in managing forest  in Perhutani areas.